2014
DOI: 10.1186/bf03352404
|View full text |Cite
|
Sign up to set email alerts
|

Shear instabilities in the dust layer of the solar nebula II. Different unperturbed states

Abstract: In the previous paper (Sekiya and Ishitsu, 2000), the shear instability in the dust layer of the solar nebula was investigated by using the constant Richardson number solution (Sekiya, 1998) as the unperturbed state, and the growth rate of the most unstable mode was calculated to be much less than the Keplerian angular velocity as long as the Richardson number was larger than 0.1. In this paper, we calculate the growth rate using different unperturbed states: (1) a sinusoidal density distribution, and (2) a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…However, the shear instability in the dust layer is not understood enough. In order to elucidate the nature of the shear-induced instability, we have performed linear calculations of the perturbation equations of the fluid mechanics in previous papers Ishitsu, 2000 and2001, hereafter referred to as Papers I and II, respectively) under the following assumptions: (1) The self-gravity is neglected. (2) A mixture of gas and dust is treated as one fluid, which is a good approximation in the case where dust aggregate sizes are small ( 1 cm).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the shear instability in the dust layer is not understood enough. In order to elucidate the nature of the shear-induced instability, we have performed linear calculations of the perturbation equations of the fluid mechanics in previous papers Ishitsu, 2000 and2001, hereafter referred to as Papers I and II, respectively) under the following assumptions: (1) The self-gravity is neglected. (2) A mixture of gas and dust is treated as one fluid, which is a good approximation in the case where dust aggregate sizes are small ( 1 cm).…”
Section: Introductionmentioning
confidence: 99%
“…
In previous our papers ( Ishitsu, 2000 and2001), hydrodynamic stability of the dust layer in the solar nebula is investigated. However, these papers neglected the rotational effects, that is, the Coriolis and tidal forces.
…”
mentioning
confidence: 99%
“…Assuming equilibrium condition for KHI, previous studies have shown that GI tends to occur if dust abundance in the protoplanetary disk is much larger than MMSN model (Sekiya 1998;Sekiya & Ishitsu 2001). Now using non-equilibrium time dependent density profile during sedimentation, we consider the possibility for GI in the case with large f d .…”
Section: Sedimentation Of Dust Grains With Single Sizementioning
confidence: 99%
“…Under the local maximum point, the Rayleigh-Taylor instability (RTI) is suspected to occur because the distribution of the gradient of dust density becomes positive (Chandrasekhar 1961). If RTI occurs, the distribution of dust density in this region is expected to be adjusted as to be constant (Sekiya & Ishitsu 2001). If it is assumed that the growth rate of RTI is larger than that of KHI, and that the distribution of dust density becomes constant around the midplane, the gradient of dust density becomes zero near the midplane.…”
Section: Possibilities Of Khi In the Early Stagementioning
confidence: 99%
“…However, vertical gradient of dust abundance is indicated to induce the vertical shear of the azimuthal velocity (Cuzzi et al 1993;Sekiya 1998), and the shear is expected to induce the Kelvin-Helmholtz instability (KHI) (Chandrasekhar 1961). KHI is expected to induce shear-driven turbulence that prevents dust aggregates from settling for GI (Cuzzi et al 1993;Sekiya 1998;Sekiya & Ishitsu 2001;Michikoshi & Inutsuka 2006). Previous studies indicate that GI tends to be occur when dust abundance is high (Sekiya 1998;Johansen & Youdin 2007).…”
Section: Introductionmentioning
confidence: 99%